Tahajiba phiranga, athavā, Angreji sabhyatā : arthāt, Angrejomse milane milāneke kāyade sarkāra darabārake niyama, sādi vivāhake ritarasasma Angreji sosāitike vyohārā ityādi ityādi (Lakshmivenkatesvara Chāpekhāne, 1972)
Manners and customs to be followed in the presence of Britishers.